SUSTAINABLE DEVELOPMENT GOALS AND QUALITY EDUCATION (Modern American Journal of Engineering, Technology, and Innovation, 2026)
The United Nations Sustainable Development Goal 4 (SDG 4) — Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all — constitutes the cornerstone of the 2030 Agenda for Sustainable Development and establishes the most comprehensive global education reform mandate in history. Yet despite nearly a decade of implementation, a profound disconnect persists between the normative aspirations of SDG 4 and the structural realities of national curriculum frameworks, teacher preparation systems, and educational governance architectures in the majority of countries. This article investigates the theoretical foundations of the SDG 4 framework, analyses the mechanisms through which national curricula either align with or diverge from SDG 4 targets, and proposes an evidence-based model for transforming curriculum frameworks to achieve genuine SDG 4 integration.